Application of Numerical Optimization to Aluminum Alloy Wheel Casting. Issue 1 (May 2015) - Duan, J; Reilly, C; Maijer, D M; Cockcroft, S L; Phillion, A B
Abstract: A method of numerically optimizing the cooling conditions in a low- pressure die casting process from the standpoint of maintaining good directional solidification, high cooling rates and reduced cycle times has been developed for the production of aluminumalloy wheels. The method focuses on the optimization of cooling channel timing and utilizes an open source numerical optimization algorithm coupled with an experimentally validated, ABAQUS-based, heat transfer model of the casting process. Key features of the method include: 1) carefully designed constraint functions to ensure directional solidification along the centerlineof the wheel; and 2) carefully formulated objective functions to maximize cooling rate. The method has been implemented on a prototype production die and the results have been tested with plant trial test.